VD_FINDINFO Jug / 2012 / 226 vom 7. März 2012 - VD Tribunal cantonal (2012)
LÉSION CORPORELLE GRAVE, NÉGLIGENCE, VIOLATION DES RÈGLES DE L'ART DE CONSTRUIRE, EXPLOSION | 125 al. 1 CP, 125 CP, 223 CP, 229 CP, 34 CP, 42 CP, 47 CP, 49 al. 1 CP, 49 CP, 50 CP